Daniel R. Turner, Grave Reminders. Comparing Mycenaean tomb building with labour and memory. - Dickinson, Oliver (Journal of Greek Archaeology, 2023)
pp. 309, 87 figures (30 colour), 12 tables, 3 appendices. Leiden: Sidestone Press, 2020. ISBN 97890-8890-9849 (hardcover); 97890-8890-9832 (softcover); 97890-8890-9856 (e-pdf). £135 hardcover, £45 softcover.